Kraft pulping from Kekabu (Ceiba pentandra) by variant alkaline active and sulphidity / Mohd Helmi Hamsin … [et al.] - Hamsin, Mohd Helmi; Abd Razak, Muhammad Syafiq; Safein, Ahmad Asyraf; Mahmud, Muhizan (2008)
This research was done on Kekabu (Ceiba pentandra) from family Malvaceae to study about the strength properties of paper and the suitability by using chemical pulping. The method that has been used is kraft pulping. The pulp that been done produced in cooking woodchips by using M K Degister. This process are distinguish between the different alkaline active and Sulfidity to determine the maximum strength of paper. From the different, the contain in alkaline active and sulfiditty that been suitable to use is 20% and 25% because it can produce the paper that have maximum strength. The paper structure, physical and mechanical like tensile strength, burst index, tearing and freeness will be tested. From the experiment, the tensile strength is 49.786 N , tearing 0.479 mN/m2g-1 , burst 4.377 kPa m2g1 , and bulk 0.904 cm2/g from here, we can indicate that the uses of differences alkaline active and Sulfidity in paper making exert influence on the paper properties itself.